THE RELATIONSHIP OF STRESS AND USE BB CREAM OF THE OCCURRENCE OF ACNE VULGARIS IN STUDENT AT UNIVERSITY OF MUHAMMADIYAH SURAKARTA FORCES MEDICAL 2018 - Ramadhina Tria Sesanti (BAPIN-ISMKI (Badan Analisis Pengembangan Ilmiah Nasional - Ikatan Senat Mahasiswa Kedokteran Indonesia), 2021)
Acne vulgaris is a skin disease that is prevalent in approximately 80-100 % of the population aged 15-18 years and over. Based on Global Burden of Disease (GBD), acne vulgaris affects 85% of young adults aged 12-25 years. This disease causes depression and anxiety. The etiology of acne is not known with certainty, but at puberty it is influenced by several risk factors, namely increased androgen hormones, use of cosmetics, personal hygiene, poor sleep patterns and stress. To determine the relationship between stress levels and use of bb cream on the incidence of acne vulgaris. The study design used a cross sectional study and it was conducted in January 2021 on students of FK UMS 2018. The subjects in this study were 33 respondents who fit the restriction criteria and the sampling used purposive sampling technique. Stress level data and use of bb cream using a questionnaire. Data on the incidence of acne vulgaris with diagnosis by a general practitioner. The data were analyzed using the test chi-square and logistic regression test. The results of the test chi-square showed a relationship between stress levels and the incidence of acne vulgaris (p = 0.001), there was a relationship between the use of BB cream and the incidence of acne vulgaris (p = 0.003). The results of the multivariate stress analysis showed a value of p = 0.010 (p <0.05) and the onset of acne vulgaris and the variable BB cream showed a value of p = 0.027 (p <0.05). There is a relationship between the level of stress and the incidence of acne vulgaris, there is a relationship between the level of stress and the incidence of acne vulgaris.